2018
DOI: 10.14814/phy2.13746
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences influence intestinal epithelial stem cell proliferation independent of obesity

Abstract: The intestinal epithelium is continuously regenerated by cell renewal of intestinal epithelial stem cells (IESCs) located in the intestinal crypts. Obesity affects this process and results in changes in the size and cellular make‐up of the tissue, but it remains unknown if there are sex differences in obesity‐induced alterations in IESC proliferation and differentiation. We fed male and female mice a 60% high‐fat diet (HFD) or a 10% low‐fat diet (LFD) for 3 months and investigated the differences in (1) the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
2
10
0
1
Order By: Relevance
“…The strong proliferative capacities of ISC and progenitors from female mice allowed the development of a higher number and size of colonoids from bottom crypts, as compared to males. This observation is in accordance with the recent data of Zhou and collaborators [25]. Moreover, this sexual dimorphism in ISC and progenitor proliferation depends on intrinsic mechanisms since the culture of epithelial cells as colonoids was exempt from stroma.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The strong proliferative capacities of ISC and progenitors from female mice allowed the development of a higher number and size of colonoids from bottom crypts, as compared to males. This observation is in accordance with the recent data of Zhou and collaborators [25]. Moreover, this sexual dimorphism in ISC and progenitor proliferation depends on intrinsic mechanisms since the culture of epithelial cells as colonoids was exempt from stroma.…”
Section: Discussionsupporting
confidence: 93%
“…We found that important regulators of the ISC proliferation (β catenin/Wnt pathway, ADAM10/Notch pathway) displayed gene overexpression in female-derived crypts compared to males. However, female- and male-derived crypts did not show significant differences in gene expression of immature markers CD44 and CD24 (our data) and in their size in vivo [25], suggesting sex-specific regulation of proliferative and differentiation pathways at the progenitor level.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar results were obtained in the study by Beyaz et al (18), in that an HFd enhanced the stemness and tumorigenicity of intestinal progenitor cells, suggesting that an HFd enhances regeneration. a recent study revealed that iScs in females have greater proliferative ability as compared with those in males (35). The results of the present study indicated that female mice fed an HFd exhibited increased iSc counts, while crypts obtained from mice fed an HFd were more likely to form mini-intestine organoids in a 3d culture, which may partially account for the increase in intestinal tumors in obese individuals.…”
Section: Discussionsupporting
confidence: 56%
“…5). По данным W. Zhou et al [38], пролиферация эпителиальных клеток тонкой кишки in vitro у мышей выше в криптах, выделенных от самок, по сравнению с криптами, выделенными от самцов. На пролиферативную активность кишечного эпителия значительное влияние оказывают глюкокортикоиды [39].…”
Section: результаты и обсуждениеunclassified